Teachers' concerns on outcomes-based education : bases for a continuing professional development plan - Olivares, Claire Anne A. (San Carlos City, Pangasinan : [s.n.], 2017)
This study sought to describe the concerns of teachers in the state universities of Tarlac province on OBE as an innovation during the school year 2016-2017, which served as bases in the development of a continuing professional development plan. This study made use of the descriptive cross-sectional design. The faculty members from the two state universities of Tarlac province, Tarlac State University and Tarlac Agricultural University, served as the respondents of this study.
Bibliography: pages 122-127.
CHED-La Union
Keywords: Professional development; Teachers